Splicing system and their variants with fuzzy algebraic sum / Mohd Pawiro Santono Othman - Othman, Mohd Pawiro Santono (2023)
This research discusses the concept of biological systems in Deoxyribonucleic Acid (DNA) which involves formal language theory namely splicing system. In DNA computing, a splicing system combines theoretical computer science and applied discrete mathematics. This splicing model is based on the recombinant behavior of DNA molecules where the model of splicing with finite components can only generate languages of lower generative power in the Chomsky hierarchy. Hence, in this research, an extension of the original models of splicing systems using fuzzy algebraic sum operation is introduced as a restriction in splicing systems and their variants to increase the generative power of the splicing languages. Moreover, the languages generated by algebraic sum fuzzy splicing systems and their variants are developed by considering the threshold and the languages generated are categorized according to the Chomsky hierarchy. An algorithm is then developed in JAVA using visual code studio software to replace the time-consuming manual computation of the languages generated by algebraic sum fuzzy splicing systems and their variants. As conclusion, it is shown that the generative power of the languages generated by algebraic sum fuzzy splicing systems and their variants are up to the context-free than those of the original splicing models. The results in a form of theorems, lemmas and corollaries are proven and presented.